Major Host Factors Involved in Epithelial Cell Invasion of Campylobacter jejuni: Role of Fibronectin, Integrin Beta1, FAK, Tiam-1, and DOCK180 in Activating Rho GTPase Rac1 - Boehm, Manja; Krause-Gruszczynska, Malgorzata; Rohde, Manfred; Tegtmeyer, Nicole; Takahashi, Seiichiro; Oyarzabal, Omar A.; Backert, Steffen (Frontiers in Cellular and Infection Microbiology, 2011)
Host cell entry by the foodborne pathogen Campylobacter jejuni has been reported as one of the primary reasons of tissue damage in infected humans, however, molecular invasion mechanisms and cellular factors involved in this process are widely unclear. Here we used knockout cell lines derived from fibronectin-/-, integrin-beta1-/- and focal adhesion kinase (FAK)-/- deficient mice and corresponding wild-type controls, to study C. jejuni-induced signalling cascades involved in the bacterial invasion process. Using high-resolution scanning electron microscopy, GTPase pulldowns, G-Lisa and gentamicin protection assays we found that each of these host cell factors is indeed required for activation of the small Rho GTPase member Rac1 and maximal host cell invasion of this pathogen. Interestingly, membrane ruffling, tight engulfment of bacteria and invasion were only seen during infection of wild-type control cells, but not in fibronectin-/-, integrin-beta1-/- and FAK-/- knockout cell lines. We also demonstrate that C. jejuni activates FAK autophosphorylation activity at Y-397 and phosphorylation of Y-925, which is required for stimulating two downstream guanine exchange factors, DOCK180 and Tiam-1, which are upstream of Rac1. Small interfering (si) RNA studies further show that DOCK180 and Tiam-1 act cooperatively to trigger Rac1 activation and C. jejuni invasion. Moreover, mutagenesis data indicate that the bacterial fibronectin-binding protein CadF and the intact flagellum are involved in Rho GTPase activation and host cell invasion. Collectively, our results suggest that C. jejuni infection of host epithelial target cells hijacks a major fibronectin>integrin beta1>FAK>DOCK180/Tiam-1 signalling cascade, which has a crucial role for Rac1 GTPase activity and bacterial entry into host target cells.